Training needs assessment of agricultural extension change agents in the field of biological control of fruit fly in Sinai Peninsula - Abdu Omran Mohamed; Yousria Ahmed Allam; Ismail Ibrahim Hassen (Bulletin of the National Research Centre, 2020)
Abstract Background The context and purpose of the study. The world has turned to the technology of organic agriculture to obtain safe food and preserve the environment, and there have become many standards that control the production, processing, and circulation of organic products. Egypt has been interested in issuing a law to control organic agriculture, and has adopted a trend toward clean agriculture based on the use of organic fertilizers and bio-control of fruit flies. The research aimed to evaluate extension activities to improve training methods in this area, so as to estimate the level of training needs of agricultural extension agents in the field of biological control of fruit flies, and determine the training methods preferred by them, identify the reasons of weak application of the methods of biological control, identify the problems faced by extension agents to transfer biological control recommendations to farmers, and to identify the relationship between the level of training needs of agricultural extension workers and some independent variables. The methodology of the study depends on theoretical and analytical methods; data were collected by personal interview using questionnaire forms Results: the main findings The main findings are summarized as follows: A It was found that more than three-quarter of change agents did not receive any training courses in this field, the attendees were low beneficiaries, so they are requiring further training in the field of biological control of fruit flies. B There are severe training needs for agricultural extension agents for the methods of biological control of fruit fly in the following: pathogenic nematodes, growth regulators and hormones of reproduction, sterilization of male insects, and pathogenic bacteria. C The agricultural extension agents prefer training methods as field visits and practical clarification D There is a direct and significant relationship between the levels of training needs and age, and there are inverse and significant relationships with experience in training, academic qualification, academic specialization, the duration of service in agricultural work, the duration of service in extension work, and the degree of job satisfaction. Conclusions a brief summary and potential implication. Potential implication is to improve the extension services based on an assessment of the change agent’s training needs, pay attention to the field demonstration in the training, and repeat it several times, and provide the trainers with auxiliary tools, while providing appropriate conditions for the fieldwork, increase agricultural programs on media broadcast to increase viewing, and support channels with research centers in order to facilitate its adoption and disseminate biological control methods in rural areas.